A Study of medication administration errors in a tertiary care hospital - S, Arun Kumar K.; K, Venkateswarlu; A, Ramesh (Indian Journal of Pharmacy Practice)
Medication administration errors account for 34% of all medication errors and identified as one of the important reasons for patients' morbidity and mortality. NPSA statistics show that 59.3% of medication errors occur during the administration stage. Thus identifying and resolving the administration errors will improve the patient care and decreases the health care costs. National Coordinating Council for Medication Error Reporting and Prevention (NCC MERP) taxonomy was used to analyse the frequency, types, severity and factors responsible for medication administration errors. The findings of the study reveal that the frequency of medication administration errors is 15.34%, omission errors (33.02%), improper dose (17.43%) and wrong time (12.84%) errors were the major types of errors occurred and the majority administration errors belonged to categoty C (112), B (46) and D (35). Frequent interruptions and distractions, lack of communication between health care professionals, performance deficit and work stress on duty nurses are identified as major factors responsible for administration errors.
Keywords: Medication Administration Errors (MAEs); National Coordinating Council for Medication Error Reporting (NCC MERP) taxonomy; National Patient Safety Agency (NPSA) and Patient Care